Barcode System Management Model on Oil Palm Company Performance: Fit Viability Approach - Zulham Zulham; Zulkarnain Lubis; Muhammad Zarlis; Ardian Arifin; Muhammad Reza Aulia (Journal Research of Social Science, Economics, and Management, 2023)
The use of innovative technology, such as the barcode system, has the potential to enhance the performance of palm oil companies. To better understand the impact of the Fit-Viability-Use barcode system on business performance, a study was conducted. This research aimed to examine the relationship between fit, viability, and use of the barcode system with business performance in the context of an oil palm company. The study utilized a sample of 237 employees, selected through stratified proportional random sampling, from PT LNK between April 2022 and June 2022. The data was analyzed using SEM-PLS analysis with SMART PLS 3 software. This paper presents an overview of the Fit-Viability approach to the Barcode System. The results showed that business performance was positively influenced by viability and use, while fit had no significant effect. The findings can be useful in further developing the barcode system at PT LNK, and it is recommended that other palm oil companies adopt this technology and integrate it into cloud-based data for real-time production data.